Analisis Penatalaksanaan Program Penanggulangan Tuberkulosis Paru dengan Strategi DOTS - Desy, Rara Jaka; Asriwati, Asriwati; Fitriani, Arifah Devi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The purpose of this study was to determine the method of case finding, to determine the management of the control program, to determine the distribution of drugs, to assess the performance of the PMO, and to determine the recording and reporting in the tuberculosis control program with the DOTS strategy. The results of this study are the method of finding pulmonary tuberculosis cases according to the SOP set by the health center, the management of the pulmonary tuberculosis control program with the DOTS strategy at the UPT Namu Ukur Health Center, Langkat Regency by implementing a pulmonary TB control program with a plan, drug distribution begins with the process of submitting a letter to the Langkat Regency Health Office, the performance of the Drug Supervisor (PMO) is good, namely motivating patients to undergo regular treatment, and nurses and analysts carry out recording and reporting by recording TB patients in a manual report book carry out the laboratory. In conclusion, the implementation of tuberculosis control with the DOTS strategy has been running well. Keywords: Management, Control, Tuberculosis and DOTS